Biosynthesis and Characterization of Silver Nanoparticles Using Parthenium hysterophorous Leaves - Ranjani1, S.; Sakthivel2, P. (Asian Journal of Chemistry, 2013)
In this work, leaf extracts of Parthenium hysterophorous were used for the generation of silver nanoparticles. The synthesized silver nanoparticles are characterized using UV visible spectrophotometer, X-ray diffractometer, IR and SEM.